ABU YAZID AL BUSTAMI DAN PENGALAMAN TASAWUFNYA - Muhammad Toriqularif (STAI AL FALAH Banjarbaru, 2018)
Abu Yazid lived in a religious family, his mother was a zahidah and his father was a leader of the community and two of his relatives including Sufi experts, although not as well known as him. At first, he studied religion at the mosque where he was born. Then he continued to travel to various regions and eventually he became a Sufi with his Sufism teachings al Fana, 'al Baqa' and al Ittihad. Before reaching the level of ittihad, he initiated his maqam with fana` and baqa` which are two inseparable twins, in the achievement of al Ittihad, al Fana` is the disappearance of basyariah traits, morals which are despised by ignorance and immoral acts of human beings. Whereas al Baqa` is the eternal nature of divinity, commendable character, knowledge and cleanliness of sin and immorality. Whereas al Ittihad is the union of the human soul with God, and to achieve this must be done maximum efforts such as repentance, remembrance, worship and adorn yourself with praiseworthy morals. A Sufi in achieving ittihad first experiences al-fana '' an al nafs, in the sense of the destruction of the soul (not the destruction of the Sufi soul becomes dead, but its destruction will lead to Sufi awareness of Himself). This is what is called the Sufis al fana'‘an al nafs wa albaqa, bi ‘l Lah, with the meaning of awareness of oneself being destroyed and self-awareness arising from God, then ittihad, unity or union with God occurs. Keywords: Abu Yazid, Sufism, al Fana,’ al Baqa,’ al Ittihad.